Cyborganic Living. (7th April 2022) - Kuptsova, Maria
Abstract: Transdisciplinary artist and researcher Maria Kuptsova works in the interstices between organic and digital systems. As she seeks new ways to design landscapes that are a rich mix of biological processes and computational algorithms and tools, she generates what she calls 'cyborganic' or 'bio‐machinic' architectural languages.